PENDAPENDAMPINGAN PETANI DALAM PENYIAPAN PESTISIDA BIORASIONAL UNTUK PENGELOLAAN HAMA DAN PENYAKIT TANAMAN AGAR MENGHASILKAN SAYURAN BEBAS RESIDU BAHAN KIMIA DAN MENDUKUNG GREEN ECONOMYMPINGAN PETANI DALAM PENYIAPAN PESTISIDA BIORASIONAL UNTUK PENGELOLAAN HAMA DAN PENYAKIT TANAMAN AGAR MENGHASILKAN SAYURAN BEBAS RESIDU BAHAN KIMIA DAN MENDUKUNG GREEN ECONOMY - Nasir, Burhanuddin Haji; Serdiati, Novalina; Tangkesalu, Dance; Lasmini, Sri Anjar (Universitas Mataram, 2024)
The cultivation of vegetable crops carried out by the community in the Transmigration Settlement Unit (UPT) Palu Valley, Central Sulawesi has been going on for a long time, but has not been able to increase their income and welfare, due to various problems faced such as: low productivity of farming which is produced because it is cultivated on dryland, pest and plant disease attacks, difficulty in obtaining inorganic fertilizers and pesticides needed during farming, and group member participation in farmer group meetings to discuss various matters of common interest within the farmer group is very low. The solution offered is to implement pest and disease control technology, organic fertilizer development technology and assistance in improving farmer group management. Community Partnership Empowerment aims to assist partner farmer groups in providing biorational pesticides made from local resources and improve management of farmer groups so that they can play an optimal role in helping farmer group members in various activities with local government. This community empowerment program was implemented at UPT Bulupountu Jaya, Sigi Biromaru District, Sulawsesi Tengah, from July to September 2024, by implementing community assistance methods to increase the knowledge and skills of participants as one of the efforts to empower partners. Implementation of training in the manufacture and development of biorational pesticides in the